VALUASI EKONOMI EKOSISTEM HUTAN MANGROVE DI KAWASAN KOTA DUMAI PROVINSI RIAU - Wahyu Novra Wanda; Aras Mulyadi; Efriyeldi Efriyeldi (Program Pascasarjana Universitas Riau, 2019)
Dumai City as an autonomous region has a strategic location with potential natural resources. With these conditions in the city of Dumai developing economic activities such as industrial estates, aquaculture, fisheries, transportation, tourism and other activities. On the other hand Dumai City also has a stretch of mangrove along the coast which is feared to experience problems due to these activities. This study aims to determine the economic value of mangrove ecosystems in Dumai City. The study, conducted in March 2019. The method used in this study is a survey method. The determination of sampling points was done by purposive sampling in 4 (four) stations: Station I (Bangsal Aceh), Station II (Muara Sungai Masjid Area), Station III (Muara Sungai Dumai), and Station IV (Tanjung Palas) Dumai City, Riau Province . The method used to estimate the economic value of resources is the Total Economic Value (TEV). WTP analysis with the Contingent Valuation Method (CVM) is likened to an approach to measure how much willing to pay. Direct use value such as the use of mangrove wood, mullet fish, shrimp, and mangrove crabs is Rp. 97,258,416,000.00 and indirect use values measured from the value of the construction of breakwaters and mangroves as nursery ground in the amount of Rp. 4,616,250,000.00. The choice of value measured from the amount of mangrove utilization as a recreation area is Rp. 1,836,000,000.00. The value of the existence and inheritance value calculated from the community's willingness to pay WTP (Willingnes To Pay) of Rp. 670,080,000.00 and Rp. 233,360,000.00, and non-use value of Rp. 893,440,000.00. So that the total economic value of mangrove forests in the coastal area of Dumai City per year is Rp. 104,604,106,000.00.